PELATIHAN POSTNATAL MASSAGE BAGI PENYANDANG DISABILITY TUNA NETRA DI HIMPUNAN WANITA DISABILITAS INDONESIA PROVINSI ACEH - Yulia Fitri; Putri Santy; Nurbaiti Nurbaiti (Universitas Majalengka, 2022)
Abstract Lack of employment opportunities is a common problem for persons with disabilities and their families. One of the ways to eliminate the negative stigma about the powerlessness of persons with disabilities is entrepreneurship. Postpartum massage can be one of the business developments for people with disabilities. The purpose of this community service activity is to increase the ability of blind persons with disabilities in postnatal massage skills so that they can develop an independent massage business by adding services in the field of postnatal massage. The methods used in this activity are lectures, demonstrations, and practicums. The training participants consisted of 10 people with visual impairments in the Indonesian Women with Disability Association (HWDI) Aceh Province. Community service activities can increase knowledge and skills in doing postnatal massage. This can be seen from the results of the average pretest score of 57.8, which then increased to 80.3 in the post-test. As for skills, in the first practicum, it reached 70% who were competent to do post-natal massage, and in the second practicum, it rose to 100%. Postnatal massage training is effective in increasing postnatal massage knowledge and skills for women with visual impairments. It is hoped that in the future empowerment activities for persons with disabilities can be carried out with a wider scope. Keywords : Disability, visual impairments, postnatal massage